Microbial hazard identification of chicken eggs produced by commercial farmers in the Bloemfontein region - Theron, Hanita (Bloemfontein: Central University of Technology, Free State, 2003)
The outbreak of disease associated with contaminated eggs is a worldwide phenomenon. In view of the high prevalence of HIV/AIDS in South Africa, it has become increasingly important to determine whether eggs posed a health risk to the consumer. Though the daily production of eggs in South Africa is in the order of 21 million, legislation regarding the safety of non-pasteurized eggs is limited. In the present study the microbiological quality of randomly selected egg samples from two different egg-producing plants in central South Africa were compared. In the investigation Pseudomonas spp, Escherichia coli, Salmonella spp, Staphylococcus spp, yeasts and moulds were tested for. Results showed that fecal-associated bacterial counts were notably higher in eggs from the system with a controlled internal environment compared to eggs from the system where no environmental control was employed. This finding was supported by the microbiological results of the bioaerosol samples. Based on these findings the recommendation was made to industry that eggs should be removed prior to the scraping of fecal material from the units. Meaningful microbial growth patterns were observed when eggs were subjected to different temperature simulations during shelf-life studies. Results indicated that a cold shock of 4 to 6 hours during transport and storage resulted in lower bacterial counts. To promote egg quality and safety, the implementation of this procedure was therefore recommended to the egg industry.
Thesis
Keywords: Poultry - Diseases - Research; Foodborne diseases - South Africa - Bloemfontein; Food - Microbiology; Eggs as food; Food contamination